Capping of the radicular exposed surface (part II). Surgical and not surgical treatment - Grados Pomarino, Sixto (2005)
The gingival recession treatment can be made surgical1y with a high predictability of success due to the great advance during the last ones of the mucogingival surgical techniques. The use of connective grafts in coverage of recessions has obtained high rates of success reason why these procedures are common within the modern periodontal surgical practice. Knowing that all patients do not accept the surgical treatment, many investigators have come studying the possibility of treating non-surgically the gingival recession by means of scale and root planing, polish and maintenance therapy showing promising results.